Designing Adaptive Learning Experiences for Generation Z in the Gig Economy - Fauzi Aldina; Seema Bholah; Lila Ramchurn (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. The expansion of the gig economy has reshaped conventional career pathways and increased the need for Generation Z to develop adaptive, digital, entrepreneurial, and self-directed career competencies. Traditional career counseling, however, often remains oriented toward occupational information and linear employment pathways. Purpose. This study aimed to design and evaluate an Adaptive Career Learning Experience (ACLE) to strengthen Generation Z’s readiness for flexible, digital, and non-traditional careers.. Method. Educational Design Research was employed through analysis and exploration, design and construction, and evaluation and reflection. Participants included 180 university students for needs analysis, seven experts for validation, 24 students for a small-group trial, and 120 students for field evaluation. ACLE was structured through five stages: Explore, Adapt, Build, Simulate, and Reflect.. Novelty. The study reconceptualizes career preparation as an instructional design framework integrating adaptive learning, authentic career simulation, digital-professional competence, entrepreneurial readiness, and reflective career planning. Results. Expert validation indicated high content validity, with Aiken’s V ranging from 0.86 to 0.94. Students participating in ACLE showed significantly greater improvements than the comparison group in career adaptability, digital career competence, entrepreneurial readiness, career self-efficacy, and gig economy career readiness (p < .001). Conclusion. ACLE offers an effective framework for shifting career preparation beyond conventional counseling toward adaptive, authentic, and experiential learning that better prepares Generation Z for digitally mediated and non-linear career environments